Analysis of machine failure codes and the impact on customer satisfaction - Bartholomay, Aaron Robert (Kansas State University, 2013)
It is challenging to know when customers are satisfied or dissatisfied with a product or service. Feedback mechanisms such as surveys are frequently used to gain feedback and evaluate the customer’s perceptions of the product or service. John Deere, like most companies, takes an active role in understanding customer satisfaction, using surveys and feedback through field teams and the dealer channel. Shortcomings with this method include the need for customers to voice their complaints first, which can take a significant amount of time, delaying John Deere from providing needed service. The purpose of this research is to examine the usefulness of using primary diagnostic data collected by John Deere to assess customer satisfaction. Specifically, to examine if the number of diagnostic trouble codes (DTCs) on a John Deere 8R series row crop tractor experiences has an impact on customer satisfaction scores reported on surveys. Then determine if this data would be useful to help identify dissatisfied customers proactively. Statistical analysis and regression were used to understand the impact DTC’s have on customer satisfaction. Analysis indicates that for every 100 Total DTC’s a machine exhibits one could expect to see a 4 point reduction in overall CSI score by the customer. This information may prove valuable in being able to understand customer satisfaction more proactively.
Keywords: Customer satisfaction; Proactive approach; Tractor; Diagnostics; Customer service; Economics, Agricultural (0503)